The Aryan clause, the Confessing Church, and the ecumenical movement: Barth and Bonhoeffer on natural theology, 1933–1935 - Ballor, Jordan J. (Scottish journal of theology, 2006)
In this article I argue that the essential relationship between Dietrich Bonhoeffer and Karl Barth stands in need of reassessment. This argument is based on a survey of literature dealing with Bonhoeffer and Barth in three basic areas between the critically important years of 1933 and 1935. These three areas come into sharp relief given the political background of the German Christian victory in the church elections of 1933. Their respective positions, both theological and political, on the Aryan clause differ greatly. For Bonhoeffer, the imposition of the Aryan clause on the German churches represented a clear status confessionis, and Bonhoeffer favoured a very public schism. For Barth, while the Aryan clause was certainly troublesome, it was deemed better to wait for a ‘more central’ point, namely, that of the question of natural theology. Barth's emphasis on the importance of the question of natural theology carries over in his position regarding the significance and role of both the Confessing Church and the ecumenical movement. We see that Bonhoeffer explicitly questions the validity of Barth's emphasis on natural theology with respect to the Confessing Church and to the ecumenical movement. While many scholars have argued for the basic agreement between Barth and Bonhoeffer, especially on the question of natural theology, a closer examination of the two in the period 1933–35 calls such conclusions into question.